STUDI TENTANG KETERAMPILAN PEMBENTUKAN KLAIM MENGENAI ISU SOSIO-SAINTIFIK SISWA SEKOLAH MENENGAH ATAS PADA KELOMPOK BUDAYA SUNDA - Bambang Ekanara; Nuryani Y Rustaman; Hernawati Hernawati (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2016)
ABSTRACTThis case study purposes to investigate Sundanese high school student 11th grade argumentation skills about socio-scientific issue based on gender and family caring pattern. Specifically, this qualitative research explores the quality of Sundanese student’ claim-forming and evidence-supplying in an argumentation process. Research instrument were given to 44 year-11 students, argumentation worksheets were used to get student’ written argumentation skills (WAS) data; semi-structured interview were used to get student’ oral argumentation skills (OAS) data; questionnaire and interview were used to get family caring pattern and family gender awareness data; furthermore, field note were used as data triangulation tool. Student’ argumentation skills were determined by justification of argument based on four-scale rubric. Inductive analysis was used to examine the data. Most Sundanese student had capable to form an argument with a simple justification; student’ OAS better than WAS relatively; and other  result of this study shows that no argumentation skills significance difference between boys and girl. The findings suggest several factors influencing Sundanese student’ argumentation skills such as freedom of opinion-forming in family life, student’ role in family, the language ability to articulate ideas, and  cultural influences. Methodological issues arising from the study and implications for teaching and assessment are discussed.